Microbial communities and nitrogen cycling in Litopenaeus vannamei and Mercenaria mercenaria polyculture ponds - Qian Liu; Xijuan Lei; Junnan Li; Luxin Chu; Fang Wang; Hongwei Shan; Fanguang Hu (Aquaculture Reports, 2023)
The nitrogen cycling has an important ecological role in aquaculture ponds, and microbes mainly carry out the related processes. To better reveal the microbial community and nitrogen cycling processes in shrimp and clam polyculture ponds, we analyzed the microbial communities of water and sediment of four ponds containing Litopenaeus vannamei with different stocking densities of Mercenaria mercenaria (LM, 0 ind/m2; LM-L, 17.4 ind/m2; LM-M, 34.8 ind/m2; LM-H, 52.2 ind/m2) from May to September. Additionally, the possible reaction rates and gene abundances involved in nitrogen cycling were determined in sediments of LM and LM-M in July. The results showed that the dominant phyla in the water included Proteobacteria, Cyanobacteria, and Bacteroidetes and in sediment were Proteobacteria, Desulfobacterota, and Chloroflexi. According to principal coordinate analysis, microbial communities of water and sediment significantly differed with and without M. mercenaria. The LEfSe analysis indicated that nitrogen cycling processes in the water of L. vannamei ponds were denitrification and dissimilatory nitrate reduction to ammonium (DNRA), while nitrification and denitrification were observed in the water of L. vannamei-M. mercenaria polyculture ponds. In the sediments of L. vannamei ponds, DNRA was dominant process, whereas in the sediments of L. vannamei-M. mercenaria polyculture ponds, DNRA, incomplete nitrification and denitrification were identified. Compared with LM, LM-M increased the nitrification rate and enhanced nitrate reduction with denitrification and anaerobic ammonium oxidation (anammox) instead of DNRA in sediments. The abundance of genes involved in nitrification and denitrification was significantly enriched in the sediments of LM-M. These results suggest that L. vannamei-M. mercenaria polyculture ponds may enhance nitrifying bacteria and denitrifiers, promoting nitrification and denitrification in sediment. This study helps understand shrimp polyculture ponds’ microbial community composition and nitrogen cycling.